1963
DOI: 10.1021/bi00905a018
|View full text |Cite
|
Sign up to set email alerts
|

The Thionicotinamide Analogs of DPN and TPN. I. Preparation and Analysis*

Abstract: The synthesis of the thionicotinamide analog of triphosphopyridine nucleotide catalyzed by pig brain transglycosidase is described. The thionicotinamide analogs of both diphospho-and triphosphopyridine nucleotide have been purified from the corresponding nicotinamide nucleotides by preparative gradient elution chromatography, and characterized by elementary analyses. The spectrophotometric constants reported are based on ribose, phosphate, and adenine analyses of the samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…Previous studies have shown that NADS and NADPS can be synthesized from thionicotinamide using porcine liver powder (Stein et al, 1963). Using an enzymatic assay, NADS can be phosphorylated to NADPS by NADK.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that NADS and NADPS can be synthesized from thionicotinamide using porcine liver powder (Stein et al, 1963). Using an enzymatic assay, NADS can be phosphorylated to NADPS by NADK.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were harvested by centrifugation (6000 g, 20 rnin), washed free of medium with 0.9 % (masshol.) NADPH stock solutions were determined spectrophotometrically at 340 nm using an absorption coefficient of 6.22X103 M-' cm-' [25] ; the thio-NADP' concentration was determined at 260 nm using an absorption coefficient of 1.95X104 M-' cm-' [26]. Cells were lysed by repeated sonication and, following centrifugation (I4 000 g, 30 rnin), the resulting cell-free extract was adjusted to 0.4 % (mass/vol.)…”
Section: Methodsmentioning
confidence: 99%
“…For calculations, absorption maxima and extinction coefficients of reduced forms of NAD + analogs were taken from the literature. 26,27 The rate of NAD + -mediated reaction was arbitrarily taken as 100%. CPAL, 3-cyanopropionaldehyde; DMABAL, N,Ndimethyl-4-aminobutyraldehyde.…”
Section: Active-site Residuesmentioning
confidence: 99%
“…6 NAD + analogs were assayed as coenzymes at a concentration of 500 μM with 1 mM APAL as a substrate. The following absorption maxima and extinction coefficients of reduced forms of these analogs 26,27 were used for calculations: NADPH, ɛ 340 = 6.62 mM − 1 cm − 1 ; thio-NADH, ɛ 400 = 11.9 mM − 1 cm − 1 ; 3-pyridinealdehyde-NADH, ɛ 358 = 9.3 mM − 1 cm − 1 , 3-acetylpyridine-NADH, ɛ 363 = 9.1 mM − 1 cm − 1 ; deamino NADH, ɛ 338 = 6.2 mM − 1 cm − 1 . Tris-HCl buffers (150 mM) in the pH range of 7.0-9.0 and glycine-NaOH buffers (150 mM) in the pH range of 8.8-10.6 were used to determine pH optimum using 1 mM APAL and 0.5 mM NAD + .…”
Section: Assays Of Activity Protein Concentration and Ion Contentmentioning
confidence: 99%